2021
DOI: 10.1111/1346-8138.15725
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive stratum corneum ceramide profiling reveals reduced acylceramides in ichthyosis patient with CERS3 mutations

Abstract: The stratum corneum (SC) of the epidermis acts as a skin permeability barrier, and abnormalities in SC formation lead to several skin disorders. Lipids, especially the epidermisspecific ceramide classes ω-O-acylceramides (acylceramides) and protein-bound ceramides, are essential for skin barrier formation. Ceramide synthase 3 (CERS3) is involved in the synthesis of acylceramides and protein-bound ceramides, and CERS3 mutations cause autosomal recessive congenital ichthyosis. In the present study, we measured c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
0
4
0
2
Order By: Relevance
“…Current scientific research does not directly describe topically applied ceramides as penetration enhancers for APIs, but their role in modulating the barrier properties of the epidermis has been confirmed. Studies have evaluated the influence of the fatty chain and the size of the polar head of ceramides on the permeability of externally applied substances, which suggests the potential for ceramides as future penetration enhancers for APIs. , In healthy human SC, ceramides contain fatty acid residue chains of more than 22 carbon atoms (Table , item 3). ,, Shorter ceramide chains are observed in dermatoses that damage the skin barrier, such as atopic dermatitis, lamellar ichthyosis, Netherton syndrome, psoriasis, and autosomal recessive congenital ichthyosis. , The effect of ceramide acyl chain length on SC barrier integrity has been confirmed in studies, in which it was observed that replacing the acyl chain in nonhydroxy acyl sphingosine-type ceramides (CER NS) of C24 length with a shorter one (C4–6) resulted in a significantly increased SC lipid permeability. An in vitro permeability study by Školova et al using Franz diffusion cells of 5% theophylline (180 g/mol, LogP = 0) and 2% indomethacin (358 g/mol, LogP = 4.3) showed that replacement of CER NS (C24) with CER NS (C6) resulted in an increase of approximately 3.5 times the permeation of theophylline and nearly 6.5 times that of indomethacin.…”
Section: Natural Components Of the Sc Are Compounds That Regulate The...mentioning
confidence: 99%
See 1 more Smart Citation
“…Current scientific research does not directly describe topically applied ceramides as penetration enhancers for APIs, but their role in modulating the barrier properties of the epidermis has been confirmed. Studies have evaluated the influence of the fatty chain and the size of the polar head of ceramides on the permeability of externally applied substances, which suggests the potential for ceramides as future penetration enhancers for APIs. , In healthy human SC, ceramides contain fatty acid residue chains of more than 22 carbon atoms (Table , item 3). ,, Shorter ceramide chains are observed in dermatoses that damage the skin barrier, such as atopic dermatitis, lamellar ichthyosis, Netherton syndrome, psoriasis, and autosomal recessive congenital ichthyosis. , The effect of ceramide acyl chain length on SC barrier integrity has been confirmed in studies, in which it was observed that replacing the acyl chain in nonhydroxy acyl sphingosine-type ceramides (CER NS) of C24 length with a shorter one (C4–6) resulted in a significantly increased SC lipid permeability. An in vitro permeability study by Školova et al using Franz diffusion cells of 5% theophylline (180 g/mol, LogP = 0) and 2% indomethacin (358 g/mol, LogP = 4.3) showed that replacement of CER NS (C24) with CER NS (C6) resulted in an increase of approximately 3.5 times the permeation of theophylline and nearly 6.5 times that of indomethacin.…”
Section: Natural Components Of the Sc Are Compounds That Regulate The...mentioning
confidence: 99%
“…Studies have evaluated the influence of the fatty chain and the size of the polar head of ceramides on the permeability of externally applied substances, which suggests the potential for ceramides as future penetration enhancers for APIs. 113 , 134 136 In healthy human SC, ceramides contain fatty acid residue chains of more than 22 carbon atoms ( Table 2 , item 3). 108 , 137 , 138 Shorter ceramide chains are observed in dermatoses that damage the skin barrier, such as atopic dermatitis, lamellar ichthyosis, Netherton syndrome, psoriasis, and autosomal recessive congenital ichthyosis.…”
Section: Natural Components Of the Sc Are Compounds That Regulate The...mentioning
confidence: 99%
“…Conversely, inflammatory skin conditions characterized by barrier abnormalities clearly show differences in the stratum corneum lipidome. Mutations in PNPLA1 alter the formation of acylceramides in ichthyosis [20 ▪ ], while the increased prevalence of short-chain ceramides observed in atopic dermatitis, psoriasis and ichthyosis modifies the stratum corneum lipid organization, and correlates with barrier dysfunction, a conclusion confirmed using model membrane systems [21,22,23 ▪▪ ,24].…”
Section: Lipids Have Different Roles Throughout the Skinmentioning
confidence: 68%
“…Вместе с тем отмечено наличие пятнистой эритемы при патогенном варианте в гене NIPAL4, выпадение волос, стойкий эклабиум -при изменениях в гене ABCA12, артрит или ограничения подвижности суставов -в генах TGM1, ABCA12, NIPAL4, онихолизисв гене SDR9C7, мономорфные коричневые пластиныв гене CYP4F22 [24]. В других исследованиях показали, что больные с двуаллельными патогенными вариантами гена CERS3 всегда имели коллодиевую мембрану при рождении, эритему и мелкие чешуйки на лице и туловище, более крупные коричневые плоские ромбовидные чешуйки с легкой эритемой на нижних конечностях, а также ладонно-подошвенную гиперлинейность, гиперкератоз [33,39] не описаны [1]. Изменения в гене ALOX12B более чем в 60% случаев ассоциируют с фенотипами PI -SICI, AсSHCB, BSI [13,42].…”
Section: клинико-генетические варианты врожденного ихтиоза несиндрома...unclassified
“…Участвует в синтезе липидов и в их метаболизме во время формирования эпидермального барьера плода, в процессах кератинизации и терминальной дифференцировки кератиноцитов. Дефект в гене приводит к нарушению указанных молекулярных процессов[31,32] LIPNЛипаза N LI, CIE Нарушение дифференцировки кератиноцитовCERS3Керамид-синтетаза 3 CERS3 LI, CIE Нарушение синтеза ацилцерамидов и связанных с белками церамидов, особенно с длинноцепочечными фрагментами[33]…”
unclassified